Application of Green Asphalt Pavement Technology in Modern Road Engineering - Yang, Jianwei (Transactions on Engineering and Technology Research, 2024)
There are environmental problems in the construction and maintenance of traditional asphalt pavement, which consumes a lot of resources and produces a variety of pollutants, especially in large and medium-sized cities, posing a threat to residents' life and urban ecology. The traditional asphalt pavement industry is facing the test, and it is urgent to explore the environmentally sustainable road construction scheme. The key path is to change the concept and study and apply green and environment-friendly asphalt pavement technology. Firstly, this paper comprehensively analyzes and summarizes the carbon emission of asphalt in the whole life cycle, and then systematically introduces three kinds of asphalt green pavement engineering technologies, namely: warm mixing asphalt mixture technology, rubber powder modified asphalt mixture technology and asphalt mixture regeneration technology. Finally, the application of the construction technology of warm mixed asphalt pavement is explained in detail. The results show that green asphalt pavement technology has great environmental, economic and social significance. In the future, the innovation of asphalt pavement technology should focus on reducing resource consumption, reducing environmental pollution and improving the recycling rate of materials during the whole life cycle.